Comparative analysis of the phenolic contents and antioxidant activities of different parts of two pomegranate (Punica granatum L.) Cultivars: ‘Tunisia’ and ‘Qingpi’ - Zhang, Huifen; Wang, Miao; Yu, Guoqiang; Pu, Jing; Tian, Kun; Tang, Xiaofu; Du, Ying; Wu, Hongxia; Hu, Jiong; Luo, Xian; Lin, Lijin; Deng, Qunxian (Frontiers in Plant Science, 2023)
Pomegranate (Punica granatum L.), with its abundant phenolic substances and strong antioxidant activity, holds significant research and utilization potential across various organs. However, there have been few studies on the phenolic content and antioxidant activity of different parts of pomegranate, especially the placenta. This study investigated the phenolic content and antioxidant activity of fruits, flowers, and leaves of two pomegranate varieties, 'Tunisia' and 'Qingpi', throughout their growth and development. Results indicated significant variations in phenolic content among different organs, with petals exhibiting the highest total polyphenol content (TPC, 49.40 mg GAE/g FW) and total anthocyanin content (TMAC, 1938.54 nmol/g FW).Placenta contained the highest levels of total flavonoids (TFC, 173.58 mg RE/g FW) and punicalagin (109.30 mg/g FW). The peel had the highest content of total flavanols (TFAC, 19.42 mg CE/g FW). Over the course of pomegranate development, total